0
$\begingroup$

I proposed my conjecture as follows:

Let $f(x)$ is a real continuous function on $[m, M]$ and $f'>0, f''>0$ on $[m, M]$, let $m \le x_i \le M$, for $i=1, 2,..., n$. Then

$$\frac{f(x_1)+f(x_2)+.....+f(x_n)}{n}-f(\frac{x_1+x_2+....x_n}{n}) \le \frac{f(M)+ f(m)}{2}-f(\frac{M+m}{2}) $$

Equality holds if only if $m=x_1=x_2=....=x_n=M$

$\endgroup$
4
$\begingroup$

This conjecture is false. E.g., let $n=3$, $m=x_1=0$, $M=x_2=x_3=3$, and (say) $f(x):=0\vee(x-2)$. Then the inequality does not hold. Replacing now $f$ by its convolution with (say) the pdf of the centered normal distribution with a small enough variance, one can satisfy the conditions $f'>0, f''>0$ on $[m, M]$, whereas, by continuity, the inequality will still be false.

For instance, if the variance of the centered normal distribution is $1/4$, then the resulting convolution, given by the formula \begin{equation} f(x)=\frac{1}{2} \left((x-2) \text{erf}\left(\sqrt{2} (x-2)\right)+x+\frac{e^{-2 (x-2)^2}}{\sqrt{2 \pi }}-2\right), \end{equation} will satisfy the conditions $f'>0, f''>0$ on $\mathbb R$ but will fail to satisfy the inequality in question.

$\endgroup$
  • 6
    $\begingroup$ Or to skip the convolution, take $n=3$, $m=x_1=0$, and $M=x_2=x_3=1$, and $f(x)=x^k$. Then the inequality reads $$\frac{2}{3} - \left(\frac{2}{3}\right)^k \le \frac{1}{2} - \left(\frac{1}{2}\right)^k$$ which is clearly false for large $k$. (Indeed, for $k \ge 4$.) $\endgroup$ – Nate Eldredge Jul 25 '16 at 2:13
  • $\begingroup$ Yes, this will also do. $\endgroup$ – Iosif Pinelis Jul 25 '16 at 2:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.